Relationships between tumor grade and neurocognitive functioning in patients with glioma of the left temporal lobe prior to surgical resection - Noll, Kyle R. (Neuro Oncol, 2015)
BACKGROUND: Various tumor characteristics have been associated with neurocognitive functioning (NCF), though the role of tumor grade has not been adequately examined. METHODS: Seventy-two patients with histologically confirmed grade IV glioma (n = 37), grade III glioma (n = 20), and grade II glioma (n = 15) in the left temporal lobe completed preoperative neuropsychological assessment. Rates of impairment and mean test performances were compared by tumor grade with follow-up analysis of the influence of other tumor- and patient-related characteristics on NCF. RESULTS: NCF impairment was more frequent in patients with grade IV tumor compared with patients with lower-grade tumors in verbal learning, executive functioning, as well as language abilities. Mean performances significantly differed by tumor grade on measures of verbal learning, processing speed, executive functioning, and language, with the grade IV group exhibiting worse performances than patients with lower-grade tumors. Group differences in mean performances remained significant when controlling for T1-weighted and fluid attenuated inversion recovery MRI-based lesion volume. Performances did not differ by seizure status or antiepileptic and steroid use. CONCLUSIONS: Compared with patients with grade II or III left temporal lobe glioma, patients with grade IV tumors exhibit greater difficulty with verbal learning, processing speed, executive functioning, and language. Differences in NCF associated with glioma grade were independent of lesion volume, seizure status, and antiepileptic or steroid use, lending support to the concept of “lesion momentum” as a primary contributor to deficits in NCF of newly diagnosed patients prior to surgery.